Formation of Spherulites in Electrodeposited Alloys Fe-Ni and Fe-Cr-Ni - Kolesnyk, Ie.V.; Girin, O.B. (Physics and Chemistry of Solid State, 2015)
With the use of the methods of scanning electron microscopy and X-ray diffractometry the distinctive features of spherulites creation during electrodeposition of Fe-Ni and Fe-Cr-Ni alloys from sulfate electrolyte on low-carbon steel substrate is analyzed. The presence of spherulites is detected not only in near-substrate layers of the deposits but also on the surface of quite thick (50 mm) coatings. The increase of the coatings thickness causes the increase of sperulites size due to their selective growth. The formation of sherulites occurs at quet high current density (10 A/dm2). It is shown that spherulites formation may happen on non-indifferent substrates. The interdependence of the processes of formation of spherulite structure and crystallographic texture of the nickel containing electrodeposited alloys is discovered. The formation of sperulites is accompanied by appearance of <111> axial texture of the coatings.